Significance of properly proportioned fly ash based blended cement for sustainable concrete structures of tannery industry. (February 2021) - Mahmud, Samira; Manzur, Tanvir; Samrose, Samina; Torsha, Tafannum
Abstract: Tannery wastewater contains several detrimental constituents that severely affect concrete durability. It can also cause soil and water pollution from discharge of untreated effluent if not properly contained. Therefore, ensuring proper protection of tannery wastewater treatment plants is of extreme importance to prevent leaching of hazardous wastewater. Properly proportioned blended cement is usually required for construction of tannery wastewater treatment plants to ensure structural stability. However, there is no definite guideline available for mix design of concrete structures exposed to tannery wastewater. In this study, effect of adding different proportions of two industrial wastes i.e. fly ash and granulated blast furnace slag with ordinary Portland cement (OPC) as supplementary cementitious material (SCM) has been investigated under tannery wastewater conditions. A total of 240 cubes and 48 mortar bars were prepared and tested under normal and simulated tannery wastewater conditions. The performance was measured in terms of compressive strength, expansion, weight loss, surface deterioration etc. Scanning Electron Microscope (SEM) images and Energy-dispersive X-ray Spectroscopy (EDS) techniques were used to observe changes in microstructure. Test results revealed that blended cement composites with fly ash and/or slag suffered less strength and weight loss under tannery wastewater as compared to OPC samples. However, only fly ash blended cement composites exhibited desired performance under expansion test. In addition, SEM images and EDS analyses confirmed lower density of ettringite and less leaching of calcium in fly ash blended mixes due to pore refinement caused by formation of secondary hydration products.